Strategi dan Upaya yang Dilakukan oleh BPJS Ketenagakerjaan Kota Medan Dalam Meningkatkan Kualitas dan Kuantitas Peserta BPJS Ketenagakerjaan di Kota Medan - Siburian, Ruth Evelonia Hariani (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
BPJS Ketenagakerjaan is a social security agency responsible for providing social protection to all workers in Indonesia, both formal and informal. This study aims to analyze the strategies and efforts undertaken by BPJS Ketenagakerjaan in Medan City to improve service quality and increase the number of participants. The research employs a qualitative method using observation, interviews, and documentation techniques to obtain in-depth and contextual data. The results indicate that BPJS Ketenagakerjaan Medan City implements various strategies, including direct visits to companies with overdue contributions and unregistered workers, socialization through neighborhood heads, and the utilization of mass media and digital platforms such as YouTube and Instagram. This comprehensive approach has successfully expanded participant reach and raised public awareness regarding the importance of social security protection for workers. Thus, BPJS Ketenagakerjaan Medan City plays a significant role in enhancing workers’ welfare through inclusive and sustainable services.